DETERMINAN VARIASI EFFECTIVE TAX RATES (ETRS) PERUSAHAAN DAN REFORMASI PAJAK: STUDI TERHADAP PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2008-2009 - Dewi Kartika Sari (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2013)
This study examines the determinants of the variability in corporate effective tax rates (ETRs) in Indonesia spanning the taxation reform. Previous studies have found that there is an association between firm size, capital structure, corporate investment decision and corporate ETRs. In this study political connection (Adkulcari et al., 2006) is added as a complement of the firm size and corporate ETRs association explanation. Our results indicate that capital structure (leverage), capital-intensity, and inventory-intensity have an association with the variability of corporate ETRs in Indonesia. The opposite sign of estimated coefficient regression of capital-intensity variable might be because there is a capital lease asset in the fixed asset component. This study failed to find the association between firm size, R&D intensity, political connection, tax reform, and ETRs.